Risk Factors of Chronic Kidney Disease in Indonesian Patients with Diabetes Mellitus - Asy Syifa Anwari Zahra; Chandrayani Simanjorang (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Chronic Kidney Disease (CKD) is a public health problem with increasing prevalence and incidence. About 1 in 3 adults with Diabetes Mellitus (DM) has CKD. This study aims to determine the risk factors for Chronic Kidney Disease in Diabetes Mellitus (CKD-DM) patients in Indonesia. A cross-sectional study was conducted with secondary data, Indonesia Basic Health Research 2018. Data analysis was carried out univariate, bivariate, and multivariate. Also, spatial analysis was carried out to map the prevalence of cases. Among 14.932 samples, the prevalence of CKD-DM in Indonesia was 1.8%. Multivariate analysis results found that gender (aPR=3.24; 95%CI 3.182-3.306), every day smoker (aPR: 2.47; 95%CI 2.415 – 2.535), someday smoker (aPR=1.93; 95%CI 1.875 – 1.987), hypertension (aPR=1.56; 95%CI 1.540 – 1.591), pre elderly (aPR=1.13 95%CI 1.098 – 1.158), elderly (aPR=0.81; 95%CI 0.790 – 0.834), exercise (aPR =1.07; 95%CI 1.055 – 1.090), and obesity (aPR=0.90; 95%CI 0.891 – 0.924) have a significant relationship with the incidence of CKD-DM in Indonesia. This study found that gender is the dominant variable in the incidence of CKD-DM in Indonesia. It is desired that healthcare providers and program makers should recognize gender differences in the progression of CKD and conduct screening program for risk factors of CKD-DM.